Science and Technology for Sustainable Development - Dawlatana, Mamtaz (Bangladesh Journal of Scientific and Industrial Research, 2019)
This Special Issue contains the abstracts from the "Science and Technology for Sustainable Development" which was held on 12-14 December 2019 at the Bangladesh Council of Scientific and Industrial Research (BCSIR), Dr. Qudrat-I-Khuda Road, Dhanmondi, Dhaka-1205, Bangladesh. Organised by the Bangladesh Journal of Scientific and Industrial Research (BJSIR). Bangladesh J. Sci. Ind. Res. 54 (Special Issue), 1-134, 2019